2020
DOI: 10.1051/0004-6361/202038710
|View full text |Cite
|
Sign up to set email alerts
|

Activity time series of old stars from late F to early K

Abstract: Context. Stellar activity strongly affects and may prevent the detection of Earth-mass planets in the habitable zone of solar-type stars with radial velocity technics. Astrometry is in principle less sensitive to stellar activity because the situation is more favourable: the stellar astrometric signal is expected to be fainter than the planetary astrometric signal compared to radial velocities. Aims. We quantify the effect of stellar activity on high-precision astrometry when Earth-mass planets are searched fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…Stellar activity also affects the astrometric signal, but for massive planets to be detected with Gaia, the amplitude of the effect is completely negligible for solartype stars. Future high-precision astrometric mission aiming to detect very low mass terrestrial planets will be sensitive to stellar activity however, but to a much lesser extent than radial velocities for similar stars and planets (Makarov et al, 2010;Lagrange et al, 2011;Meunier et al, 2020).…”
Section: Observational Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Stellar activity also affects the astrometric signal, but for massive planets to be detected with Gaia, the amplitude of the effect is completely negligible for solartype stars. Future high-precision astrometric mission aiming to detect very low mass terrestrial planets will be sensitive to stellar activity however, but to a much lesser extent than radial velocities for similar stars and planets (Makarov et al, 2010;Lagrange et al, 2011;Meunier et al, 2020).…”
Section: Observational Strategiesmentioning
confidence: 99%
“…Dumusque et al (2011) performed fits of the Harvey function for a few stars observed by HARPS, but the sample is too small to derive a trend. Meunier et al (2020) scaled it to granulation amplitude because Roudier et al (2016) showed that supergranulation appears to be related to the behavior of granulation (through the analysis of trees of fragmenting granules).…”
Section: Supergranulationmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the plotted standard deviations are affected by the jitter both on the rotational timescale discussed in Section 3.1 and on the activity timescale discussed in Section 3.2. Although the deviations tend to increase with increasing metallicity and degree of nesting, the dependence on inclination is different for σ(∆X) and σ(∆Y ), in accordance with Meunier et al 2020. Before simulating the astrometric jitter time series as it would be obtained by Gaia, we add the solar wobble caused by the Earth to the time series of daily displacements. The motivation behind considering the Sun-Earth system is to determine if the detection of Earth-mass planets in the habitable zones of stars with solar-like magnetic activity is influenced by the jitter due to magnetic activity of the host star.…”
Section: Time Series Of the Astrometric Jitter As It Would Be Obtaine...mentioning
confidence: 98%
“…Meunier et al (2019) proposed a model to simulate astrometric time series for solar-type stars. Using these simulated time series, Meunier et al (2020) quantified the effect of stellar activity on astrometric measurements, and its impact on the search for Earth-mass planets in the habitable zones of old main-sequence solar-type stars. Shapiro et al (2021, hereafter Paper I) developed a model, that employs the observed distribution of spots and faculae on the visible solar disk, to calculate the astrometric jitter of the Sun.…”
Section: Introductionmentioning
confidence: 99%